2014
DOI: 10.1104/pp.114.239137
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Evolutionary Analysis of the CASPARIAN STRIP MEMBRANE DOMAIN PROTEIN Family    

Abstract: CASPARIAN STRIP MEMBRANE DOMAIN PROTEINS (CASPs) are four-membrane-span proteins that mediate the deposition of Casparian strips in the endodermis by recruiting the lignin polymerization machinery. CASPs show high stability in their membrane domain, which presents all the hallmarks of a membrane scaffold. Here, we characterized the large family of CASP-like (CASPL) proteins. CASPLs were found in all major divisions of land plants as well as in green algae; homologs outside of the plant kingdom were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 60 publications
2
94
0
Order By: Relevance
“…Formation of a localized Casparian strip membrane domain (CSD) precedes formation of the Casparian strip and shows no lateral mobility [44 ]. CASP protein localization forms a barrier in the PM which blocks movement of lipid tracer dyes such as FM4-64 [45]. Subsequently, it has been demonstrated that the NADPH oxidase Curve-fitting FRAP data illustrates the range of mobilities in plasma membrane proteins.…”
Section: Plant Plasma Membranecompartmentalization Into Microdomainsmentioning
confidence: 97%
See 1 more Smart Citation
“…Formation of a localized Casparian strip membrane domain (CSD) precedes formation of the Casparian strip and shows no lateral mobility [44 ]. CASP protein localization forms a barrier in the PM which blocks movement of lipid tracer dyes such as FM4-64 [45]. Subsequently, it has been demonstrated that the NADPH oxidase Curve-fitting FRAP data illustrates the range of mobilities in plasma membrane proteins.…”
Section: Plant Plasma Membranecompartmentalization Into Microdomainsmentioning
confidence: 97%
“…We speculate that this method of membrane scaffold production for targeted alteration of the CW is a model for how CW modification occurs in other conditions. In addition to the CASP proteins, CASP-like (CASPL) family members are present in all land plants and have recently been shown to form membrane scaffolds [45]. Given that moss species such as Physcomitrella patens possess these proteins but do not produce lignin, it is possibly that the CASP and CASPL membrane scaffold method of CW modification can affect other CW components.…”
Section: Respiratory Burst Oxidase Homologue F (Rbohf) Is Recruited Tmentioning
confidence: 99%
“…Still, DUOX proteins are absent in plants, indicating a necessity for a flexible protein scaffold. The identified scaffold proteins belong to the CASPARIAN STRIP MEMBRANE DOMAIN PROTEIN (CASP) family, which, in Arabidopsis, has 20 members (Roppolo et al, 2014). Therefore, it would be interesting to determine which CASP-LIKE proteins might regulate ROS channeling from NADPH oxidases during leaf growth.…”
Section: Ros In the Apoplast: The Oxidant's Playgroundmentioning
confidence: 99%
“…More recently, it became obvious that membrane microdomains within a single cell are highly diverse and of different compositions (9). Generally, in the plant model, organisms' plasma membrane microdomains turned out to be important in plant defense (10,11), cell polarity (12,13), and general signaling properties of the plasma membrane (14,15).…”
mentioning
confidence: 99%